DEVELOPMENT OF A HOT (HIGHER ORDER THINKING) TEST INSTRUMENT ON WORK AND ENERGY AT SMA NEGERI 1 SIBOLANGIT T.A 2022/2023 - Tambunan, Jojor Sihol Marito; Wulandari, Dewi ((IPER) Indonesian Physics Education Research, 2022)
This study aims to develop a test instrument based on HOT (Higher Order Thinking) that meets the aspects of validity, reliability, level of difficulty, and discriminatory power. This type of research is development research with a 4-D model by Thiagarajan, including the define, design, develop, and disseminate stages. Small group tests were conducted on 10 students and large group tests were conducted on 30 students in class XI MIA 1 at SMA Negeri 1 Sibolangit. The results showed that the HOT (Higher Order Thinking) based test instrument on work and energy material consisted of 10 questions that were suitable for use, with expert validation test results obtained 80% valid items, small-scale test results obtained 83% valid items, test reliability of 0.8683 in the high correlation category, the difficulty level of the test in the medium category is 100%, the differentiability of the test in the good category is 80% and 20% is sufficient. The results of the large-scale test obtained test reliability of 0.79 with a high correlation category, the level of difficulty of the test were 70% moderate, 20% easy, and 10% difficult, and the distinguishing power of the test was 60% sufficient and 40% good.